High voltage engineering - Naidu, Prof M S.; Kamaraju, Prof V. ([S.l.] : Tata McGraw Hill Education Private Limited, 2013)
The text is meant for the senior Undergraduate or Postgraduate student of Electrical or Electrical and Electronics Engineering who has opted for a course on High-Voltage Engineering. The book discusses the state-of-the art in HVE systems in details. Written in simple and pedagogical manner, the content provides a holistic understanding to the interested reader of the inception, working principles, advantages and disadvantages of HVE principles and systems. The book has been designed keeping the industry requirements from a novice engineer in perspective and thus much care has been taken to provide the latest updates from the field.